TEACHING READING RECOUNT TEXT BY USING THIEVESSTRATEGY - Fitri Novia; Ratna Nery (Language and Education Journal, 2019)
The purposeof the study was to find out whether or not there wasasignificant differencein reading comprehension between the students who were taught by using THIEVES (Title, Heading, Introduction, Every first sentence,Visual, End of paragraph, Summary) strategy and that of those who were not.The quasi-experimental methodwas used to conduct the research. The population of the studywasall of theeighth-grade students of SMPN2 Teluk Gelam. In this study, the purposive sampling method was used.The total numbers of the samples were 62 students. The instrument of this research was30questions about recount text in the form of multiple-choice test. To analyze the data, t-test was used. Based on the result of independent sample t-test, the value of tobtainedwas 3.718 at significance level p<0.05 in two-tailed testing anddf=60, the critical value of ttablewas 2.0003. Since the value of tobtained (3.718) was higher than ttable(2.0003) and pvalue (0.000) was less than αvalue 0.05, it meantthat there was a significant difference in reading comprehensionbetween the students who were taught usingTHIEVES strategy and that of those who were not. Hence, THIEVES strategy could improve the eighth-grade students’ reading skill at SMPNegeri 2 Teluk Gelam